International Guillain-Barré Syndrome Outcome Study: Protocol of a prospective observational cohort study on clinical and biological predictors of disease course and outcome in Guillain-Barré syndrome - Jacobs, BC; Van Den Berg, B; Verboon, C; Chavada, G; Cornblath, DR; Gorson, KC; Harbo, T; Hartung, H-P; Hughes, RAC; Kusunoki, S; Van Doorn, PA; Willison, HJ; et al. (Wiley, 2017)
Guillain-Barré syndrome (GBS) is an acute polyradiculoneuropathy with a highly variable clinical presentation, course, and outcome. The factors that determine the clinical variation of GBS are poorly understood which complicates the care and treatment of individual patients. The protocol of the ongoing International GBS Outcome Study (IGOS), a prospective, observational, multicenter cohort study that aims to identify the clinical and biological determinants and predictors of disease onset, subtype, course and outcome of GBS is presented here. Patients fulfilling the diagnostic criteria for GBS, regardless of age, disease severity, variant forms, or treatment, can participate if included within 2 weeks after onset of weakness. Information about demography, preceding infections, clinical features, diagnostic findings, treatment, course, and outcome is collected. In addition, cerebrospinal fluid and serial blood samples for serum and DNA is collected at standard time points. The original aim was to include at least 1,000 patients with a follow-up of 1-3 years. Data are collected via a web-based data entry system and stored anonymously. IGOS started in May 2012 and by January 2017 included more than 1,400 participants from 143 active centers in 19 countries across 5 continents. The IGOS data/biobank is available for research projects conducted by expertise groups focusing on specific topics including epidemiology, diagnostic criteria, clinimetrics, electrophysiology, antecedent events, antibodies, genetics, prognostic modeling, treatment effects, and long-term outcome of GBS. The IGOS will help to standardize the international collection of data and biosamples for future research of GBS.